Urbanization, urban planning and development and urban governance : a reader for students - Islam, Nazrul. 1941-; University of Dhaka. Urban Studies Programme (Dhaka : Centre for Urban Studies, 2001)
Contributed papers.
Includes bibliographical references.
Keywords: Urbanization